Angle-controlled strong and weak coupling in photon molecules - Feng Xiao; Xiaoqiuyan Zhang; Yueying Wang; Xingxing Xu; Tianyu Zhang; Min Hu (Scientific Reports)
Abstract Strong light-matter coupling occurs when the rate of energy exchange between the electromagnetic mode and the molecular ensemble exceeds the competitive dissipation process. Coupled photon molecules with near-field light-matter interactions may produce new hybridized states when they reach the strong coupling region. Tunable Terahertz (THz) meta materials can be used to design sensors, optical modulators, etc., to improve imaging sensitivity and resolution. In this work, we use the scattering-type scanning near-field microscopy (s-SNOM) to demonstrate an angle-controlled coupling strength in a tunable photon molecules system. The system consists of a base waveguide layer and a single ribbon structure. By changing the in-plane angle between ribbon and incidence, the coupling strength between ribbon resonance and waveguide mode ranges from 0.03 to 0.08 THz, leading to the system’s transformation from weak to strong coupling. This work offers a new platform for actively controlling strong light-matter interaction and further applications in strong coupling.